Objectives Of Sharia And Their Role In Sustainable Human Development (Journal of the College of Basic Education, 2024)
This research examines the concepts of the purposes of Sharia law and its divisions, such as necessities (the five universals), needs, and improvements, and the relationship of each of them to sustainable human development, which God Almighty has recommended in His Book and His Prophet in his Sunni, by taking care of the human soul, taking into account its conditions from a spiritual, mental, and material standpoint, paying attention to its health, and taking care of aesthetic matters, such as taking care of the environment and its sources from the agricultural and animal standpoint.And water and attention to his preventive health condition and his psychological state because human beings are God’s creation on earth. He honored them by building it and taking care of it and provided for them with good things to live in it in peace.